Older Age, Polypharmacy, and Low Systolic Blood Pressure Are Associated With More Hypotension-Related Adverse Events in Patients With Type 2 Diabetes Treated With Antihypertensives - Ambrož, Martina; de Vries, Sieta T.; Hoogenberg, Klaas; Denig, Petra (Frontiers in Pharmacology, 2021)
Background and Aims: Low systolic blood pressure (SBP) levels while being treated with antihypertensives may cause hypotension-related adverse events (hrAEs), especially in the elderly, women, and frail patients. We aimed to assess the association between the occurrence of hrAEs and low SBP levels, age, sex, and polypharmacy among patients with type 2 diabetes (T2D) treated with antihypertensives. Methods: In this cohort study, we used the Groningen Initiative to ANalyse Type 2 diabetes Treatment (GIANTT) database which includes patients managed for T2D in primary care from the north of the Netherlands. Patients treated with ≥1 antihypertensive drug and ≥1 SBP measurement between 2012 and 2014 were included. The outcome was the presence of an hrAE, i.e. postural hypotension, dizziness, weakness/tiredness, and syncope in 90 days before or after the lowest recorded SBP level. Age (≥70 vs. <70 years), sex (women vs. men), polypharmacy (5 to 9 drugs or ≥10 drugs vs. <5 drugs), and SBP level (<130 or ≥130 mmHg) were included as determinants. Logistic regression analyses were conducted for age, sex and polypharmacy, including the SBP level and their interaction, adjusted for confounders. Odds ratios (OR) with 95% confidence intervals (CI) are presented. Results: We included 21,119 patients, 49% of which were ≥70 years old, 52% were women, 57% had polypharmacy, 61% had an SBP level <130mmHg and 5.4% experienced an hrAE. Patients with an SBP level <130mmHg had a significantly higher occurrence of hrAEs than patients with a higher SBP level (6.2% vs. 4.0%; ORs 1.41, 95%CI 1.14-1.75, 1.43, 95%CI 1.17-1.76 and 1.33, 95%CI 1.06-1.67). Older patients (OR 1.29, 95%CI 1.02-1.64) and patients with polypharmacy (OR 5-9 drugs 1.27, 95%CI 1.00-1.62; OR ≥10 drugs 2.37, 95% CI 1.67-3.37) were more likely to experience an hrAE. The association with sex and the interactions between the determinants and SBP level were not significant. Conclusions: Low SBP levels in patients with T2D treated with antihypertensives is associated with an increase in hrAEs. Older patients and those with polypharmacy are particularly at risk of hrAEs. Age, sex, and polypharmacy did not modify the risk of hrAEs associated with a low SBP level.